Pomiędzy mitem i faktem – dramaturgia rosyjska w dramatach polskich twórców - Gracla, Jadwiga (Acta Polono-Ruthenica, 2011)
The aim of this paper was to show links between Polish dramaturgy of the early 20th century and Russian dramaturgy. According to the author of this paper, such links are particularly conspi- cuous in Kwidam by J. Iwaszkiewicz, which in the present paper was compared with L. Andrey- evs The Life of Man. In the Polish playwrights text, which is formally related to Jederman Hofmannsthal, there are many references to the Russian text. In a similar way also Polish writers perceive the life of man (Przybyszewski, Niemojewski), which, as they believe, is like in Andery- evs play, that is, it is controlled by the supernatural power and its decreees.